КРИМИНАЛИСТІК СИТУАЛОГИЯНЫҢ ОБЪЕКТІЛЕРІ (Journal of actual problems of jurisprudence, 2019)
In article the basic objects criminalities situations are considered. The classification scheme of the criminal situations which are objectscriminalities of research is given.